White satin - Johansen, Iris (New York : Bantam Books, 2010)
"On the smooth, silvery surface of the ice skating rink, Dany Alexander cuts a figure of strength and fire, beauty and grace. One man alone is responsible for Dany's success: Anthony Malik, a former skating star who has managed her career for the past sixteen years. And for all that time, deep within his fortress of money, sex, and power, Anthony has found his attraction for Dany growing more intense. Now he wants Dany--not as a prodigy, but as a lover."--Cover.
National College of Business and Arts
Keywords: Man-woman relationships -- Fiction; Love stories